Harmonization of Halal Certification in Indonesia with Maqashid Syariah Principles: an In-Depth Study of Jasser Auda's System Approach - Syihabuddin, Muhammad; Suwandi, Suwandi (Sharia Faculty Islamic Economic Law Study Department, 2024)
The phenomenon of halal certification in Indonesia has become a public spotlight in the face of the complexity of the industrial world. The principle of Maqashid Sharia, which puts forward the highest goals in Islamic law to protect and promote the welfare of mankind, has become a critical foundation in the effort to achieve harmony between religious requirements and the practical needs of industry. Through a systematic system approach, Jasser Auda is expected to be the ideal foundation for integrating Islamic law based on Maqashid Sharia with halal certification. This study used a literature research method involving primary sources, namely Jasser Auda's book entitled